MODEL DEVELOPMENT FOR DYNAMIC CELLULAR MANUFACTURING SYSTEM CONSIDERING MACHINE BREAKDOWN AND ALTERNATIVE ROUTING PROCESS - Rizkia, Irma
The problem of cell formation in cellular manufacturing systems is one of the most important parts in designing Cellular Manufacturing systems (CMS) in which machines are grouped in cells and parts are grouped in a family part requiring costs that can be used. Various kinds of aspects have been approved in the composition of manufacturing cells, but the most important thing in the design is to consider the damage to the engine and alternative routes while in fact many of them improve it during the production process in a manufacturing company. In this model, to install systems that are subject to engine approval, alternative process routes and storage of supports on machines that repair damaged damage can reduce the detrimental effects of the production process. These problems can affect the total cost of production, taking into account such matters the total production costs can be reduced so as to produce a minimum total system cost. This problem is presented with the branch and bound method and the Mixed Integer Linear Programming (MILP) solution with the aim of achieving the total total cost of the system. Sensitivity analysis is used to prove the validity of the proposed model. In addition, examples are presented in this study.